Social-economical development in Egypt in the period of 1970-1990 - Zhanataeva, K. B. (Journal of Oriental Studies, 2016)
In this article the author considers the social-economic development in Egypt in the period of 1970-1990. It was necessary to conduct complex reform, for their effectiveness in order to develop economy of the country.